2020
DOI: 10.3390/molecules25245916
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Biological Activity and Phenolic Composition of Ethanol Extracts of Pomegranate (Punica granatum L.) Peels

Abstract: Pomegranate (Punica granatum L.) is a rich source of constituents with confirmed strong biological activities. However, pomegranate peel, which encompasses approximately 30–40% of its weight, is treated as a biological waste. The aim of this paper was to evaluate the potential of pomegranate peel extracts and to propose its functional properties that can be used for development of functional products. Eight ethanol extracts of pomegranate peels (PPEs) were characterized by use of direct infusion quadrupole-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
4
18
0
2
Order By: Relevance
“…Studies in the literature used several different forms of extract, including ethanolic, methanolic, and water. Our results were in agreement with other published data, most of which showed the most beneficial health effects following treatment with ethanolic extracts [ 38 , 75 , 76 ]. In general, pomegranate peel extract has been confirmed as a highly valuable source of bioactive compounds that can be used to improve the functional characteristics of food when used in ethanolic form [ 76 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Studies in the literature used several different forms of extract, including ethanolic, methanolic, and water. Our results were in agreement with other published data, most of which showed the most beneficial health effects following treatment with ethanolic extracts [ 38 , 75 , 76 ]. In general, pomegranate peel extract has been confirmed as a highly valuable source of bioactive compounds that can be used to improve the functional characteristics of food when used in ethanolic form [ 76 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our results were in agreement with other published data, most of which showed the most beneficial health effects following treatment with ethanolic extracts [ 38 , 75 , 76 ]. In general, pomegranate peel extract has been confirmed as a highly valuable source of bioactive compounds that can be used to improve the functional characteristics of food when used in ethanolic form [ 76 ]. The mix of flavonoids, polyphenols, and other active ingredients found in pomegranate peel have been published previously, confirming that the antioxidant activity in the pomegranate can be attributed mainly to its polyphenol, quercetin, and rutin contents [ 77 ].…”
Section: Discussionsupporting
confidence: 94%
“…A similar trend was observed with the results obtained by Li et al [ 57 ] and Sabraoui et al [ 3 ], who found that the reducing power of a peel extract was higher than that of an aril extract. Zeljka et al also reported that peel extracts exhibit strong antioxidant activity (100.25–176.60 μmol Trolox Eq/100 g) in reducing the Fe(III)-TPTZ complex [ 58 ]. The reducing power of pomegranate fruit parts is probably due to the action of the hydroxyl groups of phenolic compounds, which may act as electron donors.…”
Section: Resultsmentioning
confidence: 99%
“…Vildan et al (2020) studied the anti‐inflammatory activity of punicalagin to evaluate the in vitro oral wound healing effect of angarin combined with zinc. Peršurić et al (2020) revealed the anti‐bacterial activity of punicalin through PLS‐DA experimental analysis. Chukwuma et al (2020) confirmed the anti‐diabetes and anti‐oxidation properties of gallic acid from propanol extract of PP. The comprehensive utilization value of pomegranate can be improved by extracting effective substances from PP.…”
Section: Discussionmentioning
confidence: 99%
“…studied the anti-tumor activity of punicalagin and discussed its anti-proliferation mechanism on A549 cell line and MRC-5 cell line Vildan et al (2020). studied the anti-inflammatory activity of punicalagin to evaluate the in vitro oral wound healing effect of angarin combined with zinc Peršurić et al (2020). revealed the anti-bacterial activity of punicalin through PLS-DA experimental analysis Chukwuma et al (2020).…”
mentioning
confidence: 99%